THE EFFECT OF CONSUMER BEHAVIOR ON ONLINE PURCHASE DECISION (CASE STUDY ON UNIVERSITAS HASANUDDIN STUDENTS) - Zaky , Muhammad Ainun; Asdar, Muhammad; Ismail , Muhammad (Accounting Profession Journal (APAJI), 2024)
The rapid growing of e-commerce industry accompanied by major increase in internet users and changing in consumer behaviour in Indonesia make online purchase trend become more widespread. This research aimed to identify the effect of consumer behaviour on online purchase decision. This study examines how cultural factor, social factor, and psychological factor affecting online purchasing decision. Survey research method is used by distributing structured questionnaire to a sample size of 108 respondents from Universitas Hasanuddin students. This research used Multiple Regression Model and data was processed through SPSS 23. The result of this study showed that cultural and social factor has no significant effect on online purchasing decision. In other hand, this research found that online purchasing decision is significantly affected by psychological factor.